Equity crowdfunding, shareholder structures, and firm performance. (26th September 2018) - Walthoff‐Borm, Xavier; Vanacker, Tom; Collewaert, Veroniek
Abstract: Research question/issue: This paper provides a first‐time glimpse into the postcampaign financial and innovative performance of equity‐crowdfunded (ECF) and matched nonequity‐crowdfunded (NECF) firms. We further investigate how direct and nominee shareholder structures in ECF firms are associated with firm performance. Research findings/insights: We find that ECF firms have 8.5 times higher failure rates than matched NECF firms. However, 3.4 times more ECF firms have patent applications than matched NECF firms. Within the group of ECF firms, we find that ECF firms financed through a nominee structure make smaller losses, whereas ECF firms financed through a direct shareholder structure have more new patent applications, including foreign patent applications. Theoretical/academic implications: Our findings suggest that there are important adverse selection issues on equity crowdfunding platforms, although these platforms also serve as a catalyst for innovative activities. Moreover, our findings suggest that there is a more complex relationship between dispersed versus concentrated crowd shareholders and firm performance than currently assumed in the literature. Practitioner/policy implications: For policy makers and crowdfunding platforms, investor protection against adverse selection will be important to ensure the sustainability of equity crowdfunding markets. For entrepreneurs and crowd investors, our study highlights how equity crowdfunding and the adopted shareholder structure relate to short‐term firm performance.